Using documentary film texts as authentic input in enhancing second language (Arabic) writing skills - Tg. Abdul Rahman, Tengku Ainul Farha; Chik, Abdul Rahman; Sahrir, Muhammad Sabri (Faculty of Languages and Communication, Universiti Sultan Zainal Abidin, 2015)
The objectives of this paper are two folds: firstly, to highlight the studies using authentic input in teaching second language skills, and secondly to offer ways to deal with authentic materials in Arabic as a Second Language (ASL). For this purpose, the paper analyses related literature review and give some suggestions on how to design ASL teaching materials for learners of writing skills. The literature review showed the concern of second language practitioner as well as scholars of the field. In contrast, studies related to ASL in this topic very rare. There are 4 steps to be adopted for the purpose of linking authentic material input with enhancing writing skills output. So, this on-going research will be benefited from this review and soon apply in ASL setting. The paper also highlights the strengths of authentic input in teaching languages as well as putting some technical advice and suggestions to improve the teaching material selection.